Dataset on the optimization of a photovoltaic solar water pumping system in terms of pumping performance in remote areas of Phayao province using response surface methodology - Nopparat Suriyachai; Torpong Kreetachat; Phanintra Teeranon; Punjarat Khongchamnan; Saksit Imman (Data in Brief, 2024)
The Response Surface Methodology (RSM) was employed to examine the impact of the pumping system in a photovoltaic solar water pumping system, while operating under ideal conditions. The input parameters for optimizing the pump performance of the PV water pump include three parameters: Solar irradiance (550–950, W/m2), temperature (30–45, °C), and voltage (420–540, V). The experimental values of PV water pump efficiency showed that the efficiency of PV water pumps was in the range of 55.24–80.80% of the experiment. At a solar irradiance of 750 W/m2, a voltage of 480 V and a temperature of 37.5 °C shows the maximum efficiency of the solar PV water pump systems was 80.80% under optimal conditions. This work demonstrates the potential of solar water pumps as a reliable, cost-effective, and environmentally friendly solution to support agriculture in remote areas. In addition, the costs and economic parameters of solar photovoltaic water pumps and conventional systems were compared by the social return on investment (SROI) evaluation. This indicates that sales are profitable or create social value that benefits society and local stakeholders in remote areas. This work demonstrates the potential of solar water pumps as a reliable, cost-effective, and environmentally friendly solution to support agriculture in remote areas.